A new species of Nebalia (Crustacea, Leptostraca) from a hydrothermal field in Kagoshima Bay, Japan - Hirata, Takuma (Zookeys, 2019)
Abstract. A new species of Leptostraca, Nebalia tagirisp. nov. is described and illustrated. This species was sampled from 200 m depth at a hydrothermal field in Wakamiko Caldera of Kagoshima Bay, Japan. Nebalia tagirisp. nov. is different from known Nebalia species as follows: rostral length 2.4 times as long as width; article 4 of antennule with 3–5 robust distal spines; antennular scale approximately twice as long as wide; article 3 of antenna with eight spines and nine spine-like setae along proximal half, two thin setae and six spine-like setae on external lateral face, six spines and four simple setae on distal margin; article 1 of second maxilla longer than article 2; article 2 of mandibular palp with two thin setae; exopod of pleopod 1 with 21 spines along lateral margin; furcal rami longer than combined length of pleonite 7 and telson; rounded denticles of pleonite 6 and 7; anal-plates ‘shoulder’ not distinct. Furthermore, this specimen is the first genus Nebalia found in the hydrothermal vent. The distribution and ecology of this new species is also discussed and a key to all species of Nebalia is provided.